KETERBACAAN ARTIKEL KESEHATAN VIRUS MONKEYPOX DI WEBSITE KEMENKES RI PERIODE 2022-2023: (Readability Research dengan Metode Flesch Reading Ease dan Cloze Procedure) - Ficka Destriana Putri; Kayla Cahya Kinasih (Jurnal Komunikasi & Media Digital, 2025)
This study aims to measure the readability level of health articles on the Monkeypox virus published on the official website of the Indonesian Ministry of Health (www.kemkes.go.id) during the 2022–2023 period. A descriptive quantitative approach was applied using readability techniques. The unit of analysis included three selected educational articles. Primary data were collected through the Flesch Reading Ease (FRE) formula to analyze text structure and a Cloze Procedure test involving 30 early adults (ages 20–31) who completed missing words in the text. The results show that all three articles were categorized as “very difficult” based on FRE scores (–4.07; –38.29; –23.86), while Cloze Procedure scores indicated high reader comprehension (429–456), falling into the “easy to understand” category. These findings highlight a discrepancy between technical linguistic complexity and readers' ability to interpret messages, supported by textual redundancy. This study recommends that the Ministry simplify sentence structure, add glossaries for medical terms, and consider appropriate readability formulas for the Indonesian language context. Future research is encouraged to explore alternative methods and include broader demographic groups.